Motivation For The Decision To Visit Tourists At The Telaga Tourism Destination During The Peak Of Bogor - Amrina Rosyada; Rianto Rianto; Fifi Nofiyanti; R.M.W. Agie Pradhipta; Maria Junetha Sihasale (Jurnal Mirai Management, 2023)
This study aims to (1) to analize the motivation of tourists at the tourist destination of Puncak Puncak Bogor Lake (2) to analize the decision of tourists to visit the tourist destination of Puncak Bogor Lake (3) to analize the influence of motivation on the decision to visit tourists at the Puncak Bogor tourist destination. The approach to this study uses a quantitative approach with survey research methods. The population used in this study is visitors to the tourist destination of Telaga Saat Puncak, Bogor. The data collection method was carried out using observation, interviews, and questionnaires. The sample tested was 100 people with the Slovin formula taking the technique. This study uses the analytical method Validity Test, Descriptive Statistics, Correlation Coefficient Analysis, Determination Coefficient, Simple Linear Regression, T-Test using the SPSS 24 analysis tool. From the test results of the coefficient of determination it is known that motivation has an effect of 63.2% on decision making to visit a tourist destination. Time Lake. While the remaining 36.8% Tourist Visit Decisions are influenced by factors other than the variables used in this study. Keywords: Motivation, Visiting Decisions, Tourist Destinations